Bacteremia caused by a novel Bordetella species, "B. hinzii". - Cookson, B T (1994)
Bordetella spp. cause respiratory tract diseases in warm-blooded animals. Only Bordetella bronchiseptica has been reported to cause bacteremia in humans, and this rare infection usually occurs with pneumonia in immunocompromised patients. We describe "Bordetella hinzii" bacteremia in an AIDS patient without a respiratory illness. Combining biochemical phenotyping with fatty acid analysis permitted preliminary identification of this previously undescribed pathogen; identity was confirmed by DNA-DNA hybridization. This report extends the spectrum of human infections caused by the bordetellae.